LEUKOCYTES DIFFERENTIATION OF Pangasius hypopthalmus THAT WERE FEED WITH CURCUMIN EXTRACT FROM Curcuma domestica V - Iman, Khasan Nur; Riauwaty, Morina; Syawal, Henni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted on June until August 2016 in Parasites and Fish Diseases Laboratory, Faculty of Fisheries and Marine science, University of Riau, Pekanbaru. The aim of this research was to determine leucocyte differentiation of Pangasius hypopthalmus that were feed with curcumin extract from Curcuma domestica V. This research used five treatment such as; Kn (negative control): that were feed without curcumin extract and were not infected with A. hydrophila, Kp (positive control): that were feed without curcumin extract and infected with A. hydrophila, P1: feed with curcumin extract in 0,3g/kg, P2: feed with curcumin extract in 0,5g/kg and P3: feed with curcumin extract in 0,7 g/kg. Fish reared in an aquarium the size of 40x30x30 cm with stocking density 10 fish / aquarium, feeding as many as 10% of body weight and do 3 times a day. Pisciculture carried out for 30 days and after that fish infected with Aeromonas hydrophila. The results shown that P3 (feed with curcumin extract in 0,7 g/kg) were the best treatment with lymphocytes 83,00%; monocytes 5.33%; neutrophils 3,67%; thrombocyte 8.00%; total leukocytes 12,01x104 cell/mm3; and fagocyte index 58,33.Keyword: Leukocytes, Pangasius hypopthalmus, Curcuma domestica V, Curcumin Extract